Job satisfaction of Malaysian registered nurses: A qualitative study - Atefi, N.; Abdullah, K.L.; Wong, L.P. (Wiley, 2016)
Background: Job satisfaction is an important factor in health care settings. Strong empirical evidence supports a causal relationship between job satisfaction, patient safety and quality of care. However, there have not been any studies exploring the job satisfaction of Malaysian nurses. Aim: The main purpose of this qualitative descriptive study was to explore the factors related to feelings of job satisfaction as well as job dissatisfaction experienced by registered nurses in Malaysia. Method: A convenient sample of 46 Malaysian nurses recruited from a large hospital (number of beds = 895) participated in the study. A total of seven focus group discussions were conducted with nurses from surgical, medical and critical care wards. A semi-structured interview guide was used to facilitate the interviews, which were audio-recorded, transcribed verbatim and checked. The transcripts were used as data and were analysed using a thematic approach. Finding: The study identified three main themes that influenced job satisfaction: (1) nurses' personal values and beliefs; (2) work environment factors and (3) motivation factors. Concerning the nurses' personal values and beliefs, the ability to help people made the nurses felt honoured and happy, which indirectly contributed to job satisfaction. For work environment factors, team cohesion, benefit and reward, working conditions play an important role in the nurses' job satisfaction. Motivation factors, namely, professional development and clinical autonomy contributed to job satisfaction. Conclusion: It is important for nurse leaders to provide more rewards, comfortable work environments and to understand issues that affect nurses' job satisfaction. Relevance to clinical practice: Our findings highlight the importance of factors that can improve nurses' job satisfaction. The study provides basic information for hospital administrators in planning effective and efficient policies to improve nursing job satisfaction in order to increase the quality of patient care and decrease nursing turnover.